International perspectives in online instruction - Hoffman, Jaimie; Blessinger, Patrick (Innovations in higher education teaching and learning., 2021)
Focusing on effective practices in online teaching, this volume of Innovations in Higher Education Teaching and Learningbegins with discussing the use of videos in online teaching and then pivots to consider methods for supporting and managing faculty who teach online.